Sosialisasi Strategi Pemasaran dengan Menerapkan Bauran Pemasaran (7P) untuk Peningkatan Penjualan CV. Pandu Wisata Edutama - Agus Susanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
CV Pandu Wisata Edutama is a MSE that produces and markets the Shan Shan Water brand. Business location in Kandri Village RT. 05 RW. 01, Kandri Village. Gunungpati District, Semarang City, Central Java Province. UMK Shan Shan Water has had a business license since August 3 2020. Shan Shan Water produces demineralized drinking water. The aim of the activity is: To provide an understanding of the concept of marketing strategy, and to be able to apply the marketing mix (7P) in the sale of Shan Shan Water drinking water, so that it can increase sales of CV Pandu Wisata Edutama. The method for carrying out activities is interactive lectures, namely the method used to convey material by presenting and explaining the material that has been prepared. Discussion method, namely the resource person and participants conduct a dialogue about Marketing Strategies to Increase CV Sales. Edutama Tourist Guide. Question and answer method, which is used to determine participants' responses and level of understanding. Socialization activities on marketing strategies for Shan Shan Water drinking water products provide additional knowledge about strategies in marketing demineralized drinking water products. It is hoped that training activities can increase knowledge in developing marketing strategies so that they can increase CV sales. Edutama Tour Guide. Knowledge of marketing strategies is expected to be able to become capital for managers and employees in marketing products